A Critical Examination of Popular Assumptions About the Benefits and Outcomes of Monogamous Relationships. (May 2013) - Conley, Terri D.; Ziegler, Ali; Moors, Amy C.; Matsick, Jes L.; Valentine, Brandon
In this article, we critically examine the social institution of monogamy. First, we discuss the lack of an adequate and consistent definition of the construct of monogamy and consider how common monogamy is. Next, we address perceived benefits of monogamy and whether those ostensible benefits are supported by empirical evidence. We conclude that evidence for the benefits of monogamy relative to other relationship styles is currently lacking, suggesting that, for those who choose it, consensual non-monogamy may be a viable alternative to monogamy. Implications for theories of close relationships are discussed.